The body in Limbo: Bronzino, the Dante illustrators and the iconography of Inferno IV - Gaston, Robert (Spunti e Ricerche, 2016)
Like the apocryphal gospels which sought to satisfy the believer’s curiosity about the silences in canonical texts, Bronzino’s Christ in Limbo takes the beholder into experiences only hinted at in Dante’s text. The painter’s friends are here not just witnesses, they are actors, as were Dante and Virgil in the Divine Comedy. Dante is implicitly present in the picture only as auctor of the poem which the painter seeks both to possess and to surpass. Bronzino’s embodiment of leading Dante scholars into his iconography signifies not just his own literary competence and social affiliation with Dante scholarship. His Christ in Limbo pictorially represents his own scholarship in practice.